Developing digital teaching material on Basic Electricity based on problem-based learning in vocational education - Sulaeman Deni Ramdani; R. Ahmad Zaky El Islami; Herlina Pratiwi; Moh Fawaid; Haris Abizar; Ismi Maulani (Jurnal Pendidikan Vokasi, 2021)
The electrical topic is considered a material that is difficult to understand because electricity is a substance that is not seen but can be felt. The objectives of this study were 1.) to develop digital textbooks for basic electricity materials based on problem-based learning; 2.) to analyze the feasibility of digital textbook products for basic electricity materials based on problem-based learning. This research is development research using the 4D model, namely define, design, develop, disseminate. This study involved language, material, and media experts in validating research products. The research subjects were students of technical engineering vocational education in one of the public universities in Indonesia who took Basic Electrical and Electronics courses, namely 25 students. The data collection technique used interviews, document analysis, and questionnaires. The data analysis technique used descriptive statistical analysis. Based on the research results that have been done, it has resulted in several conclusions, namely; 1.) Development of digital textbooks on basic electricity materials based on problem-based learning is carried out by referring to the 4D model development steps, namely define, design, develop, and disseminate; 2.) The appropriateness of digital textbooks according to the media expert's assessment of getting a mean score of 3.61 is declared very good, the material expert's assessment is 3.52, which is declared very good, and the user response gets an assessment of 3.51, which is declared very good Theoretically developed digital textbooks are able to increase student interest and motivation to learn basic electrical materials in an easy way.